2017
DOI: 10.1108/mi-12-2015-0099
|View full text |Cite
|
Sign up to set email alerts
|

Growth kinetic and composition of the interfacial layer for RF sputtering Al2O3layer on germanium

Abstract: Purpose-The quality of GeOx-Ge interface and the equivalent oxide thickness (EOT) are the main issues in fabricating high-k/Ge gate stack due to the low-k of GeOx interfacial layer (IL). Therefore, a precise study of the formation of GeOx IL and its contribution to EOT is of utmost importance. In this study, the GeOx ILs were formed through post-oxidation annealing of sputtered Al 2 O 3 on the Ge substrate. The purpose of this paper is to report on growth kinetics and composition of IL between Al 2 O 3 and Ge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…This allows the sputtering material to enter the deep positon of the cellulose substrate easily. Compared with literature [37,38], the “appearance deposition rate” for the deposition layer was higher here, at a rate of about 0.90 μm/min. It was found that the wide range of blending area for the Al 2 O 3 and cellulose material contributed a lot to the “appearance thickness” and “appearance deposition rate”.…”
Section: Resultsmentioning
confidence: 54%
“…This allows the sputtering material to enter the deep positon of the cellulose substrate easily. Compared with literature [37,38], the “appearance deposition rate” for the deposition layer was higher here, at a rate of about 0.90 μm/min. It was found that the wide range of blending area for the Al 2 O 3 and cellulose material contributed a lot to the “appearance thickness” and “appearance deposition rate”.…”
Section: Resultsmentioning
confidence: 54%
“…In our previous study, we have shown that the Chlorine (Cl) termination after HCl treatment on Ge surface was confirmed by Cl2p spectra of XPS measurement and this can prevent slightly the intermixing between Ge and Al 2 O 3 after PDA of 400°C (Sahari et al 2017b(Sahari et al , 2017a. In this study, we continue the study by investigating on the effect of Cl-termination by increasing the temperature up to 600°C.…”
Section: Introductionmentioning
confidence: 67%